2023
DOI: 10.1080/26415275.2023.2244982
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride exchange by glass-ionomer dental cements and its clinical effects: a review

John W. Nicholson,
Sharanbir K. Sidhu,
Beata Czarnecka

Abstract: The topic of fluoride release and uptake by glass-ionomer (glass polyalkenoate) dental cements is reviewed. The study was based on a literature search carried out using PubMed. The main key words used were glass-ionomer and fluoride , and further refinements were made by adding the keywords anti-microbial , anti-caries and remineralization . Papers were selected from the initial search, which conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…This was in accordance with a previous study [ 52 ] and a consensus that ranked EF and F9 as the first and third materials of choice among conventional GICs for long-term restorative materials [ 53 ]. The level of fluoride release was governed by several key factors, such as the composition of the glass, the porosity and solubility of materials, the molecular weight of a polyacid, and the powder-to-liquid ratio [ 35 , 54 , 55 ]. EDX analysis of the powder phase showed that EF and F9 contained higher levels of fluoride compared with other materials., which may partly explain the higher level of fluoride release observed with EF and F9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was in accordance with a previous study [ 52 ] and a consensus that ranked EF and F9 as the first and third materials of choice among conventional GICs for long-term restorative materials [ 53 ]. The level of fluoride release was governed by several key factors, such as the composition of the glass, the porosity and solubility of materials, the molecular weight of a polyacid, and the powder-to-liquid ratio [ 35 , 54 , 55 ]. EDX analysis of the powder phase showed that EF and F9 contained higher levels of fluoride compared with other materials., which may partly explain the higher level of fluoride release observed with EF and F9.…”
Section: Discussionmentioning
confidence: 99%
“…It was, however, suggested that fluoride at a concentration of 0.03–0.7 ppm could inhibit mineral loss and enhance remineralization in dentin [ 10 ]. This may be associated with the reduction of S. mutans and inhibits the bacteria from metabolizing carbohydrates [ 55 , 61 ]. Furthermore, all tested materials provided elemental release other than fluoride, such as Al, Sr, and P. A high level of elemental release was generally observed in EF.…”
Section: Discussionmentioning
confidence: 99%
“…Two distinct factors seem to be critical for the clinical efficacy of GIC materials: the release of ions [ 14 ] and the mechanical properties [ 15 ]. Although the minimum local concentration of fluoride release required to inhibit the progression of caries has not been determined, reinforcement with various particles alters the composition of GIC and may affect the potential for ion release [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dental cements represent restorative materials composed of small biomolecules that demonstrate biocompatibility and contribute positively to tooth structure. These materials ideally possess qualities such as tooth adhesion, antimicrobial attributes, and resilience against masticatory forces during normal function and parafunction [ 5 ]. Glass ionomer cement (GIC), also known as “polyalkenoate cement”, is among the earliest dental cements with the unique attributes of fluoride release and adherence to tooth structure [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%